Pengaruh Arus Kas, Profitabilitas Dan Leverage Terhadap Financial Distress Saat Masa Pandemi Pada Perusahaan Manufaktur Terdaftar Di BEI - Aminar Sutra Dewi; Fajri Arianto; Rida Rahim; Jefri Winanda (Politeknik Ganesha Medan, 2022)
Financial distress is a condition where a company experiences problems with their finances so that the company is threatened with bankruptcy. This study aims to determine and analyze the effect of cash flow, profitability and leverage variables partially on financial distress, as well as to determine which variable has most dominant influence on financial distress in manufacturing companies. The data processed is secondary data from the annual report of 30 manufacturing companies listed on the IDX in 2016-2021 which were taken through purposive sampling. The method use in this research is panel data regression analysis method using Eviews version 10. The result of this study indicate that : cash flow has a negative effect on financial distress, profitability and leverage have a significant effect on financial distress. Keywords: Financial distress, cash flow, Profitability, leverage